Development of E-Modules Based on Exe-Learning on Topics of Reaction Rate Against Student Learning Outcomes Mechanical Engineering - Mastiur Verawaty Silalahi (IJECA (International Journal of Education and Curriculum Application), 2020)
The research was conducted at the University of HKBP Nommensen Pematangsiantar. The purpose of this research: (1) to determine the feasibility analysis of the feasibility of developing the exe-learning media on the reaction rate material by expert validators, (2) to determine the student's response to the feasibility of developing the ex-learning media on the reaction rate material, and (3) To determine the effect of the use of exe-learning media on the learning outcomes of mechanical engineering study program students at University of HKBP  Nommensen Pematangsiantar. Data collection techniques using a questionnaire. And data processing using descriptive methods. Based on the results of this researches; (1) The level of feasibility analysis according to expert validator for the development of exe-learning media on the rate material is said to be a valid media category because the overall percentage of each overall assessment of the four aspects of development is 87.20% and lies in the range of  80% until 100% with a valid category, (2) Student responses to the level of feasibility of developing ex-learning media on the reaction rate material said the media category was valid because the average percentage of each overall from the assessment of the four aspects of development was 86.35% and located in the range of 80% until 100% with a valid category. And (3) Learning outcomes using exe-learning media are higher than using power points (contextual) with 80% and 66% increase in learning outcomes.